A strategy of ultrasound-assisted processing to improve the performance of bio-based coating preservation for refrigerated carp fillets (Ctenopharyngodon idellus). (30th May 2021) - Yu, Dawei; Zhao, Wenyu; Yang, Fang; Jiang, Qixing; Xu, Yanshun; Xia, Wenshui
Highlights: Ultrasound was an effective auxiliary measure for COS coating preservation. Ultrasound assisted COS (COS-UA) coating retarded the quality loss of fillets. Microbial composition of refrigerated fillets treated with coatings were analyzed. Spoilage bacteria including Aeromonas and Shewanella were inhibited after coatings. The shelf life of refrigerated fillets was prolonged by 5 days after COS-UA coating. Abstract: Effects of ultrasound-assisted chitooligosaccharides (COS-UA) coating on the quality attributes and microbial composition of refrigerated grass carp fillets were evaluated. The results showed that COS and COS-UA coatings retarded quality deterioration of fillets during storage. Compared to COS coatings, COS-UA treated samples had lower contents of BAs, simultaneously their levels of total volatile base nitrogen (TVB-N), K value and total viable counts (TVC) were further decreased by 13.6%, 4.2% and 7.8% on day 12, respectively. High-throughput sequencing showed that Aeromonas and Shewanella increased rapidly in control samples and became the main microbiota at day 12. By contrast, both coatings changed the microbial composition and reduced the proportion of spoilage organisms. Based on multiple evaluations, COS-UA extended shelf life of fillets by another 2 days when compared to COS. Therefore, ultrasonic treatment could be considered as an effective supplementary to improve the preservation effect of COS-based coatings for fresh preprocessed fish.